Perceptions of ultra processed food are associated with strategies for identifying healthy foods in online survey of adults living in Vermont - Rose, Nick; Kolodinsky, Jane (Frontiers in Public Health, 2025)
IntroductionThe public health effects of industrial food processing are being widely researched, in response to observational evidence linking ultra processed food (UPF) consumption with a range of poor health outcomes. While there has been global debate regarding whether UPF should be incorporated into dietary guidelines for the public (in addition to existing nutrient recommendations) there is a limited understanding of the degree to which consumers prioritize food processing attributes, relative to nutrient attributes (e.g., sugar, sodium, saturated fat) when making decisions about food and health. This study investigates how perceptions of UPFs relate to the criteria that consumers prioritize when evaluating food healthfulness, including both nutrient-based and non-nutrient-based attributes.MethodsAn online survey was conducted in 2022 with a sample of 671 adults residing in a northeastern U.S. state. The survey assessed perceptions of UPFs, including efforts to reduce UPF consumption, and the importance assigned to various nutrient (sugar, fat, sodium, and food groups) and non-nutrient (kitchen ingredients, minimal processing, and production practices) criteria in determining food healthfulness. Demographic variables included age, gender, income, education, race/ethnicity, and presence of children in the household. Multivariate logistic regression analyzed associations between UPF perceptions and healthfulness criteria, reported as adjusted odds ratios (AORs).ResultsA slight majority (52%) of respondents were familiar with the term “ultra-processed foods,” with awareness significantly higher among females (p < 0.05). Twenty-one percent of respondents selected all nutrient criteria as indicators of healthfulness, while 79.1% selected at least one non-nutrient criterion. Respondents actively trying to reduce UPF consumption (33.5%) were less likely (p < 0.05) to prioritize nutrient-based criteria and more likely to prioritize non-nutrient factors, including kitchen ingredients (AOR: 1.6, 95% CI: 1.1–2.4), processing (AOR: 3.0, 95% CI: 2.0–4.5), and production practices (AOR: 1.8, 95% CI: 1.2–2.6).DiscussionFindings suggest that perceptions of UPFs shape how consumers define healthy food, with many favoring non-nutrient criteria related to processing and production over conventional nutrient profiles. This shift in consumer perspective highlights the importance of incorporating processing-related information into public health communication and food labeling strategies.